(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Mulberry; nutritional food value; leaf blight disease; Phyllosticta sp.; silkworm Bangladesh j. genet. biotechnol. 5 (1&2): 73-77, 2004 (June & December)